DEVELOPMENT OF THE EDUCATIONAL PROCESS BASED ON INNOVATIVE APPROACHES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the process of developing innovative pedagogical technologies and their introduction into the educational process, as well as the rapid exchange and improvement of information technologies, each teacher must develop their professional training, pedagogical skills. This article presents some of the problems and their solutions in the use of modern pedagogical technology.